Aquatic monocotyledons of North America : ecology, life history, and systematics - Les, Donald H. (Boca Raton, FL : CRC Press, 2020)
This book brings together information on the natural history, ecology and systematics of North American aquatic monocotyledons. The book is an overview of the biology of major aquatic species by compiling information from numerous sources that lie scattered among the primary literature, herbarium databases, and other reference sources. Information on more than 300 species in 87 genera of monocotyledons will be included. Recent phylogenetic analyses will be incorporated. Although focusing specifically on North America, the cosmopolitan distribution of many aquatic plants should make this an attractive text to people working virtually anywhere outside of the region as well. Key Selling Features: The primary source of natural history information on aquatic plants Comprehensive lists of ecological associates Synthetic overview of systematic relationships of aquatic species and genera Practical information for rare and invasive plant managers Essential guide to facilitate wetland delineation
OCLC-licensed vendor bibliographic record.
Keywords: Monocotyledons -- North America; Aquatic plants -- North America; NATURE / Ecology; SCIENCE / Life Sciences / Botany; SCIENCE / Environmental Science